Exploring the pattern of price interdependence in rice market in Indonesia in the presence of quality differential - Anisa Dwi Utami; Harianto Harianto; Bayu Krisnamurthi (Cogent Economics & Finance, 2023)
Being the main food commodity, the dynamics of rice prices is one of the most important issues for Indonesian economy. The prices at the retail level and at the farm level are influenced not only by the demand and supply in each of these markets but also by price behavior at the wholesale market. This study aims to analyse the dynamics of the relationship and behaviour of the prices of various varieties and qualities of rice in the wholesale market. The dynamics of rice prices are investigated by employing multivariate vector error correction model (VECM) and using daily price series at wholesale level during the period of 1 October 2014 until 12 February 2018. The results show a strong price relationship between premium-quality rice and medium-quality rice and between medium-quality rice and low-quality rice. Changes in the price of premium-quality rice and changes in the price of low-quality rice will have a large influence on the price of medium quality rice, but not vice versa. Furthermore, regarding the price stabilization policy, the results suggested that the policies aimed at regulating medium-quality rice prices are estimated to have relatively weak effects on the prices of premium-quality rice and low-quality rice.
Keywords: C320; Q110; Q130; 330; Food price; Price transmission; Rice; VECM; Wholesale market